Title: what about my voice? Autistic young girls' experiences of mainstream school. Issue 4 (8th August 2019) - Goodall, Craig; MacKenzie, Alison
ABSTRACT: Recognition of inclusion in mainstream schools for all people with disabilities is enshrined in the Convention on the Rights of Persons with Disabilities (CRPD). General Comment 4 on Article 24 (Right to inclusive education) of the CRPD provides a concept of inclusion and its core features which we discuss here. Article 7 of the same enjoins state parties to give young people's opinions and views 'due weight' on matters that affect them. Despite calls to gather their views on education to better inform policy and practice, autistic young people have been largely missing from the research, girls most notably. Research on the efficacy of mainstream inclusion and the educational experiences of autistic young people has focused mainly on the perspectives of adult stakeholders such as parents, teachers and classroom assistants. Inspired by Article 7 of the CRPD, we present the educational experiences of two teenage girls with Asperger's Syndrome in a mainstream setting in the UK with respect to the school environment, teachers, the curriculum and peers. The findings from semi-structured interviews and a number of participatory methods reveal that girls reported feelings of exclusion, isolation and anxiety. We discuss these findings in the light of the concept of inclusion provided in the General Comment and conclude with the girls' recommendations on how to include people with ASD in mainstream settings.